2008
DOI: 10.1038/mp.2008.100
|View full text |Cite
|
Sign up to set email alerts
|

Population-based linkage analysis of schizophrenia and bipolar case–control cohorts identifies a potential susceptibility locus on 19q13

Abstract: Population-based linkage analysis is a new method for analysing genomewide single nucleotide polymorphism (SNP) genotype data in case-control samples, which does not assume a common disease, common variant model. The genome is scanned for extended segments that show increased identity-by-descent sharing within case-case pairs, relative to case-control or control-control pairs. The method is robust to allelic heterogeneity and is suited to mapping genes which contain multiple, rare susceptibility variants of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 21 publications
3
28
0
Order By: Relevance
“…Substantially, larger samples than the one used in our study would also allow testing the common disease-rare variant hypothesis (CDRV) through direct detection of CNVs as well as through other methods such as the population-based linkage analysis of SNP genotypes. 72 In addition, to fully capture the genetic architecture of MDD the analysis of genes would have to include the interaction with known environmental risk factors for MDD (for example, childhood abuse and stressful life events 71,73,74 ). In summary, considerable hope has relied, and continues to rely on human genetics for improving disease prevention and treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Substantially, larger samples than the one used in our study would also allow testing the common disease-rare variant hypothesis (CDRV) through direct detection of CNVs as well as through other methods such as the population-based linkage analysis of SNP genotypes. 72 In addition, to fully capture the genetic architecture of MDD the analysis of genes would have to include the interaction with known environmental risk factors for MDD (for example, childhood abuse and stressful life events 71,73,74 ). In summary, considerable hope has relied, and continues to rely on human genetics for improving disease prevention and treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased transporter expression would therefore be expected to reduce glutamate signaling. Interestingly, the human VGLUT1 gene maps to chromosome 19q13, a possible susceptibility locus for schizophrenia (Hamshere et al, 2005;Francks et al, 2010). Furthermore, both VGLUT1 polymorphisms (Shen et al, 2009) and decreased hippocampal VGLUT1 expression have been reported in schizophrenia, particularly in older patients (Eastwood and Harrison, 2005;Sawada et al, 2005;Piyabhan and Reynolds, 2006), where they may contribute to cognitive dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is noteworthy that human RyR genes, RYR1 and RYR3, are encoded at sites, 19q13 and 15q14–15, respectively, which have been implicated as risk loci for bipolar disorder in genome-wide association studies (Reif et al, 2004; Francks et al, 2010; Green et al, 2013). Alternatively, these targets may be involved in side effects of ADs such as ventricular tachycardia (Thanacoody and Thomas, 2005; Zima et al, 2008).…”
Section: Drug Elucidation Drives Discovery Researchmentioning
confidence: 99%